Internal control and competitiveness in the Empresa Eléctrica Regional del Sur S.A. from Ecuador - Morales Espinosa, Judith María (2018)
The thesis titled “Internal Control and Competitiveness in Empresa Eléctrica Regional del Sur” S.A., Ecuador, period 2012-2014”, allowed to meet the problems found in the company, concerning to the lack of control in the Operational Management sector. In order to be competitive and fulfill its obligations such as a good Customer Service, we have applied the methodology of scientific investigation. We have used the survey as a technique for collecting information directly from public and workers as well as professional experts who have a direct or indirect relationship with the company. The thesis was developed with the collection of information and data from different specialists, who contributed to consolidate the development of the variables: Problems regarding to implementation of internal control, and competitiveness in EERSSA, located in the City of Loja in Ecuador. The technique of survey with twelve (12) questions allowed to obtaining data. The information allowed the tabulation and work in the graphic formulation, with their respective interpretations; the hypothesis was carried out to determine the conclusions and recommendations. Finally, it was determined that the implementation of internal control positively influences the profitability of the company.